Observation of Tool Life of Micro End Mills - Martin, Blair; Morrow, Justin; Heaney, Patrick; Pfefferkorn, Frank (8th International Conference on MicroManufacturing (ICOMM 2013), 2013)
Prediction of mechanical machining tool life is an integral part of commercial manufacturing. Failure of micro end mills is still not well understood, and further work needs to be done to accurately predict tool life. The objective of this study is to observe the distribution of tool life for micro end mills under aggressive machining conditions without lubri-cation for 300-um-diameter micro end mills while machining 6061-T6 aluminum alloy. The average tool life was 3 to 7 times greater for the nanocrystalline diamond (NCD) coated micro end mills as compared with the uncoated (as received) tools. For both NCD coated and uncoated micro end mills the tool life increased as the cutting speed was in-creased from 32 to 48 m/min, suggesting the presence of a built-up-edge during machining. The variance in the tool life data was approximately an order of magnitude greater than what is expected in macro-scale machining.
Keywords: tool life; nanocrystalline diamond; coating; micro end milling